2013
DOI: 10.1109/ted.2013.2270893
|View full text |Cite
|
Sign up to set email alerts
|

New Analysis Method for Time-Dependent Device-To-Device Variation Accounting for Within-Device Fluctuation

Abstract: Variability of nanometer-size devices is a major challenge for circuit design. Apart from the as-fabricated variability, the postfabrication degradation introduces a timedependent variability, originating from statistical distribution of charge location and number. The existing characterization techniques do not always capture the maximum degradation. Some of them does not separate the device-to-device variation from the charging fluctuation within the same device, either. The objective of this paper is to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 23 publications
(37 reference statements)
1
35
0
Order By: Relevance
“…2(a). When there are more than 3 traps in a device, however, the step-like Id switching generally is replaced by a complex within-a-device-fluctuation (WDF) [12], as shown in Fig. 2(b).…”
Section: Defects Responsible For Rtnmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a). When there are more than 3 traps in a device, however, the step-like Id switching generally is replaced by a complex within-a-device-fluctuation (WDF) [12], as shown in Fig. 2(b).…”
Section: Defects Responsible For Rtnmentioning
confidence: 99%
“…As device sizes are downscaled to the nanometer range, both Random Telegraphy Noise (RTN) and Negative Bias Temperature Instability (NBTI) can adversely affect the pMOSFET and, in turn, circuit performance and they have attracted a lot of attentions [1][2][3][4][5][6][7][8][9][10][11][12]. The relationship between RTN and NBTI is not fully understood, although it was suggested that they are the two facets of the same mechanism [1].…”
Section: Introductionmentioning
confidence: 99%
“…For nanometer devices, individual-charging/discharging can be observed and Fig.5 shows that NBTI-induced aging at a given stress time is no longer a fixed value [19][20][21][22]. It consists of two components: a winthin-a-device fluctuation (WDF) and a lower-envelop (LE) that does not discharge [19][20][21][22].…”
Section: Within a Device Fluctuation (Wdf)mentioning
confidence: 99%
“…It consists of two components: a winthin-a-device fluctuation (WDF) and a lower-envelop (LE) that does not discharge [19][20][21][22]. The upper panel in Fig.…”
Section: Within a Device Fluctuation (Wdf)mentioning
confidence: 99%
See 1 more Smart Citation